MECHANISMS OF STATE FINANCIAL SUPPORT OF INNOVATIONS IN THE SERVICE SECTOR IN UZBEKISTAN - Djalilov Faxriddin Azimovich (Modern American Journals, 2025)
This article analyzes the essence and practical effectiveness of the mechanisms of state financial support of innovative activities in the service sector in Uzbekistan. In particular, the impact of mechanisms such as subsidies, tax incentives, state grants, preferential loans and investment guarantees on the innovative development of service enterprises is scientifically studied. It also highlights the economic results of existing support measures, their role in increasing employment, and their importance in ensuring the quality and competitiveness of services. The article develops scientific conclusions based on the analysis of statistical data, state programs and practical experience.
Keywords: Service sector, innovation, state support, financial mechanisms, subsidies, tax incentives, state grants, preferential loans, investment guarantees, economic efficiency, employment, competitiveness, state policy, quality of services, economic development